Design, recruitment, and baseline characteristics of the EMPA-KIDNEY trial - Herrington, William G.; Hauske, Sibylle J. (Nephrology, dialysis, transplantation, 2022)
The effects of the sodium-glucose co-transporter 2 inhibitor empagliflozin on renal and cardiovascular disease have not been tested in a dedicated population of people with chronic kidney disease (CKD).The EMPA-KIDNEY trial is an international randomized, double-blind, placebo-controlled trial assessing whether empagliflozin 10 mg daily decreases the risk of kidney disease progression or cardiovascular death in people with CKD. People with or without diabetes mellitus (DM) were eligible provided they had an estimated glomerular filtration rate (eGFR) ≥20 but <45 mL/min/1.73 m2 or an eGFR ≥45 but <90 mL/min/1.73 m2 with a urinary albumin:creatinine ratio (uACR) ≥200 mg/g. The trial design is streamlined, as extra work for collaborating sites is kept to a minimum and only essential information is collected.Between 15 May 2019 and 16 April 2021, 6609 people from eight countries in Europe, North America and East Asia were randomized. The mean age at randomization was 63.8 years [standard deviation (SD) 13.9)], 2192 (33%) were female and 3570 (54%) had no prior history of DM. The mean eGFR was 37.5 mL/min/1.73 m2 (SD 14.8), including 5185 (78%) with an eGFR <45 mL/min/1.73 m2. The median uACR was 412 mg/g) (quartile 1-quartile 3 94-1190), with a uACR <300 mg/g in 3194 (48%). The causes of kidney disease included diabetic kidney disease [n = 2057 (31%)], glomerular disease [n = 1669 (25%)], hypertensive/renovascular disease [n = 1445 (22%)], other [n = 808 (12%)] and unknown causes [n = 630 (10%)].EMPA-KIDNEY will evaluate the efficacy and safety of empagliflozin in a widely generalizable population of people with CKD at risk of kidney disease progression. Results are anticipated in 2022.
Mit einer graphischer Zusammenfassung
Online veröffentlicht: 3. März 2022
The EMPA-KIDNEY Collaborative Group, Writing Committee: William G. Herrington, Christoph Wanner, Jennifer B. Green, Sibylle J. Hauske, Parminder Judge, Kaitlin J. Mayne, Sarah Y.A. Ng, Emily Sammons, Doreen Zhu, Natalie Staplin, David Preiss, Will Stevens, Karl Wallendszus, Rejive Dayanandan, Carol Knott, Michael Hill, Jonathan Emberson, Susanne Brenner, Vladimir Cejka, Alfred K. Cheung, Zhihong Liu, Jing Li, Peiling Chen, Laiseong Hooi, Wen Liu, Takashi Kadowaki, Masaomi Nangaku, Adeera Levin, David Cherney, Roberto Pontremoli, Aldo Pietro Maggioni, Shinya Goto, Aiko Tomita, Rajat Deo, Katherine Tuttle, Jens Eilbracht, Stefan Hantel, Mark Hopley, Martin J. Landray, Colin Baigent, Richard Haynes
Gesehen am 23.01.2024